Investigating the Impact of Sex Hormones on Obesity-Related Secondary Infertility in Women - Saba Sabeeh Hussein (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Secondary infertility remains a significant reproductive health concern worldwide, and obesity has emerged as an important factor associated with endocrine and metabolic disturbances that may compromise female fertility. Specific Background: Obesity has been linked to alterations in gonadotropin secretion, thyroid function, prolactin levels, and lipid metabolism; however, evidence regarding these associations among women with secondary infertility remains limited. Knowledge Gap: Data evaluating hormonal and metabolic differences between obese and non-obese women with secondary infertility, particularly in Iraqi populations, are scarce. Aims: This study aimed to compare reproductive hormones, thyroid function, prolactin levels, and lipid profiles between obese and non-obese women diagnosed with secondary infertility. Results: Obese women demonstrated significantly lower luteinizing hormone and thyroid-stimulating hormone levels, together with significantly higher total cholesterol and triglyceride concentrations than non-obese women. Prolactin levels were elevated in both groups without significant between-group differences. Age-adjusted analyses confirmed the persistence of the luteinizing hormone and lipid profile differences. Body mass index correlated with triglycerides in obese women and with cholesterol in non-obese women. Novelty: The study provides evidence from a carefully selected secondary infertility cohort while excluding major confounding reproductive and endocrine conditions. Implications: The findings support the incorporation of early body mass index assessment, metabolic screening, and weight-management strategies into the evaluation and management of secondary infertility. Keywords: Secondary Infertility, Obesity, Luteinizing Hormone, Lipid Profile, Reproductive Endocrinology Key Findings Highlights Reduced gonadotrophin concentrations were identified among participants with elevated body mass index. Metabolic abnormalities were characterized by increased cholesterol and triglyceride concentrations. Age-adjusted analyses confirmed the robustness of the endocrine and biochemical differences.